Strategies of Increasing The Growth and Results Pakcoy by Modification of Media and Nutrition in The Axis System Hydroponic (Wick System) - Made Riski Darmawan; Candra Ginting; Ryan Firman Syah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
This study seeks to determine the growth response and yield of Pakcoy plants grown in various nutrient concentrations and growing media types. This study employs a wick system and the split-plot method, which consists of the main plot, which is the Ab mix nutrition with three nutrient concentrations: 5 ml (N1), 7.5 ml (N2), and 10 ml (N3). The subplot is comprised of three kinds of planting media: Rockwool (M1), husk charcoal (M2), and cocopeat (M3). These two parameters were obtained through nine different treatment combinations. Each treatment was administered three times. The research data were analyzed with a split-plot design at a significance level of 5%. Followed by Duncan's test with a 5% significance level if there is a treatment difference. The results demonstrated a significant interaction between nutrient concentrations and the type of growing medium on the parameters of the number of leaves, plant dry weight, root fresh weight, root dry weight, root dry weight, root fresh weight, root fresh weight, root dry weight, crown fresh weight, and shoot dry weight. The results demonstrated a significant interaction between nutrient concentrations and the type of growing medium. The optimal treatment combination was found for all parameters at a nutrient concentration of 10 ml with Rockwool growing media.